2007
DOI: 10.1186/1472-6963-7-84
|View full text |Cite
|
Sign up to set email alerts
|

Priority setting in the provincial health services authority: survey of key decision makers

Abstract: Background: In recent years, decision makers in Canada and elsewhere have expressed a desire for more explicit, evidence-based approaches to priority setting. To achieve this aim within health care organizations, knowledge of both the organizational context and stakeholder attitudes towards priority setting are required. The current work adds to a limited yet growing body of international literature describing priority setting practices in health organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 22 publications
7
40
0
Order By: Relevance
“…Both academic opinion, and many assessments of what decision makers view as the ‘ideal’, support the idea of more formalized resource allocation processes in the health sector [16,20,37-39]. In our survey, about half of respondents claimed to observe formal processes of resource allocation at the senior management level.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Both academic opinion, and many assessments of what decision makers view as the ‘ideal’, support the idea of more formalized resource allocation processes in the health sector [16,20,37-39]. In our survey, about half of respondents claimed to observe formal processes of resource allocation at the senior management level.…”
Section: Discussionmentioning
confidence: 64%
“…Literature suggests that in Canada and elsewhere, healthcare organizations typically allocate resources on the basis of historical patterns –‘locking in’ to past budget choices [26] -- and/or political rationales [7,33,34], and there are powerful institutional and cultural reasons why this is so [35,36]. However, senior decision makers reportedly desire increased formalization or rationality in priority setting practice [16,20,37-39]. Our aim in the survey was to explore the balance between these different modes in a quantifiable way.…”
Section: Introductionmentioning
confidence: 99%
“…International studies examining PHC and hospital management teams found competency gaps in planning and priority setting, which have negative consequences for health service delivery (7, 25, 43, 48). Studies in LMICs note that planning and priority setting is a skill confined to lists of activities rather than coordinated processes with measurable outcomes and procedures for monitoring performance of PHC clinics (7, 49).…”
Section: Discussionmentioning
confidence: 99%
“…We purposively sought informants who had previous exposure to formal priority setting processes -in this case, with the PBmA framework, which has been used widely by decision-makers in British Columbia and elsewhere (dionne et al 2008;Teng et al 2007;urquhart et al 2008;Patten et al 2006;Halma et al 2004) -and those who had not had such exposure. decision-maker partners in the two health authorities helped us identify and approach potential participants.…”
Section: Methodsmentioning
confidence: 99%